The effect of achieving guideline-based target low-density lipoprotein cholesterol levels on mortality in transcatheter aortic valve implantation patients with coronary artery disease - Demir, Ömer Furkan; Levent, Fatih (The European Research Journal, 2023)
Objectives: The aim of this retrospective study was to evaluate the effects of bringing low-density lipoprotein cholesterol (LDL-C) values to levels in line with guideline recommendations on long-term mortality in patients with a known history of coronary artery disease (CAD), undergoing transcatheter aortic valve implantation (TAVI), and long-term pre-treatment with statins. Methods: This is a retrospective and observational study of patients undergoing TAVI at a tertiary heart center with a history of CAD and long-term statin therapy. Ninety-nine patients were included in the study. The relationship between LDL-C levels in accordance with the guidelines and 5-year mortality was determined by regression analysis. Results: When the study population was divided into 2 groups with and without 5-year mortality, LDL-C values were found to be significantly higher in the mortality group (120 mg/dL vs. 93.9 mg/dL, p < 0.001). Parameters associated with the development of 5-year mortality were evaluated with univariate and multivariate logistic regression analysis. LDL-C ≥ 100 mg/dL (OR: 6.59, 95% CI: 2.17-20.01) and LDL-C ≥ 70 mg/dL (OR:3.88, 95% CI: 1.16-12.93) parameters were determined as independent predictors of mortality independent of other parameters. Conclusions: The most important result obtained in this study is that achieving the LDL-C level targets specified in the guidelines significantly reduces the in-hospital and 5-year mortality rates in patients with a previous history of CAD and statin use and undergoing TAVI. Although all patients included in the study used statins, the mortality rate was significantly higher in patients who did not reach the target LDL-C value.